2016
DOI: 10.1002/cam4.693
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative frozen section analysis of the proximal bile ducts in hilar cholangiocarcinoma is of limited value

Abstract: Frozen section analysis (FS) during cancer surgery is widely used to assess resection margins. However, in hilar cholangiocarcinoma (HCCA), FS may be less reliable because of the specific growth characteristics of the tumor. The aim of this study was to determine the accuracy and consequences of intraoperative FS of the proximal bile duct margins in HCCA. Between 1990 and 2014, 67 patients underwent combined extrahepatic bile duct resection and partial liver resection for HCCA with the use of FS. Sensitivity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 27 publications
1
16
2
3
Order By: Relevance
“…The sensitivities and specificities of intraoperative frozen section analyses for cholangiocarcinoma were reportedly 68–97% and 97–98%, respectively, in previous studies . These results, combined with the present study, were deemed reliable enough for decision‐making regarding additional resection during surgery.…”
Section: Discussionsupporting
confidence: 73%
“…The sensitivities and specificities of intraoperative frozen section analyses for cholangiocarcinoma were reportedly 68–97% and 97–98%, respectively, in previous studies . These results, combined with the present study, were deemed reliable enough for decision‐making regarding additional resection during surgery.…”
Section: Discussionsupporting
confidence: 73%
“…Для 2-го периода (начавшегося с 2004 г.) характерно значительное увеличение числа больших резекций печени с желчными протоками по сравнению с изолированными резекциями желчных протоков ввиду понимания того, что ВХ не является «местным» опухолевым процессом, а носит региональное распространение с инфильтративным ростом вдоль желчных протоков [16].…”
Section: материал и методыunclassified
“…Although the sensitivity and specificity of intraoperative frozen section analysis are very limited [18,19], routine frozen section examination is still very important. Studies have shown that when a positive margin is diagnosed, 54%-83% patient can still get R0 margin after further resection [18,[20][21][22] and prognosis may improve [15,20,23].…”
Section: Introductionmentioning
confidence: 99%